Combined scanning X‐ray diffraction and holographic imaging of cardiomyocytes. Issue 2 (29th March 2017) - Nicolas, Jan-David; Bernhardt, Marten; Krenkel, Martin; Richter, Claudia; Luther, Stefan; Salditt, Tim
Abstract : This article presents scanning small‐angle X‐ray scattering (SAXS) experiments performed on the actomyosin assemblies in freeze‐dried cardiac muscle cells by scanning the sample through a sub‐micrometre focused beam. The scanning SAXS experiments were advantageously combined with full‐field holographic imaging to complement the X‐ray diffraction with real‐space imaging. Abstract : This article presents scanning small‐angle X‐ray scattering (SAXS) experiments on the actomyosin assemblies in freeze‐dried neo‐natal rat cardiac muscle cells. By scanning the cells through a sub‐micrometre focused beam, the local structure and filament orientation can be probed and quantified. To this end, SAXS data were recorded and analyzed directly in reciprocal space to generate maps of different structural parameters (scanning SAXS). The scanning SAXS experiments were complemented by full‐field holographic imaging of the projected electron density, following a slight rearrangement of the instrumental setup. It is shown that X‐ray holography is ideally suited to complete missing scattering data at low momentum transfer in the structure factor, extending the covered range of spatial frequencies by two orders of magnitude. Regions of interest for scanning can be easily selected on the basis of the electron density maps. Finally, the combination of scanning SAXS and holography allows for a direct verification of possible radiation‐induced structural changes in the cell.